(untitled) (Annals of Medical Research, 2023)
Aim: The aim of our study is to determine the clinical-pathological features of conjunctival lesions operated in a tertiary-care hospital in the eastern region of our country over a 10-year period. Materials and Methods: Demographic data of the patients and histopathological findings in the conjunctival biopsy specimens that were sent to our pathology laboratory between January 2010 and July 2020 were retrospectively analyzed. Lateralization, localization, distribution rates and frequency of lesions in different histopathological subgroups according to age and gender were evaluated. Results: 286 conjunctival biopsy materials from 272 patients were analyzed. The age of the patients ranged from 1 to 95, and the mean age was 50.39±23.59. One hundred and sixteen (43%) of the patients were female and 156 (57%) were male. Of the lesions, 144 (50.3%) were located in the right eye, and 142 (49.7%) were located in the left eye. In our series, the most common lesion was pterygium with a rate of 33.9%, and the second most common conjunctival lesion was nevi with a rate of 19.2%. Nevi were the most common melanocytic lesion with a rate of 93.2%. Melanocytic lesions are the most common lesions in childhood and adolescence, with a significant decrease in incidence with increasing age. Degenerative lesions were seen in all age groups, they were most common over the age of 45 (n:76, %78). In the 46-65 age groups pterygium was the most common lesion among all groups with a rate of 40.2%. Among epithelial neoplastic lesions, benign lesions, premalignant lesions, and malignant lesions were detected with a rate %2.4 %16.4, and %3.5 respectively. Most of the lesions were located in the bulbar conjunctiva (87.4%). This was followed by tarsal (5.2%), caruncle/fornix (4.9%) and limbus (2.4%) locations, respectively. Conclusion: Melanocytic lesions are more common in the first two decades, and degenerative lesions are commonly seen after the 4th decade. In advanced ages (over 65 years), premalignant and malignant lesions are seen at a very high rate. Pterygium is accompanied by CIN with a rate of 7% and all conjunctival lesions should be directed to the pathology laboratory for histopathological examination.